A 'new' economic history of the Middle East and North Africa (MENA) region1. Issue 2 (April 2017) - Saleh, Mohamed
Abstract: This article argues that there is a need to develop a 'new' economic and social history of the Middle East and North Africa (MENA) region that is based on exploiting novel sources of data, including (a) primary papyrological sources from the medieval period, (b) primary sources at the region's local archives and European (colonial) archives, and (c) primary sources from the ancient (pre‐Islamic) period. The proposed 'new' history of the MENA region must be inter‐disciplinary for two reasons: (a) digitizing and employing these novel data sources in research requires the collaboration of social scientists, historians, archaeologists, anthropologists, demographers and papyrologists, as well as the co‐operation of MENA‐based scholars who have better access to MENA's local archives, and (b) even if these novel sources are digitized, data limitations are likely to impose a constraint on the reach of quantitative analysis and thus necessitate an inter‐disciplinary methodology that combines quantitative evidence with historical analysis.